The proteome of neural stem cells from adult rat hippocampus - Maurer, Martin H.; Feldmann, Robert Enrico; Fütterer, Carsten Dietmar; Kuschinsky, Wolfgang (Proteome science, 2003)
Hippocampal neural stem cells (HNSC) play an important role in cerebral plasticity in the adult brain and may contribute to tissue repair in neurological disease. To describe their biological potential with regard to plasticity, proliferation, or differentiation, it is important to know the cellular composition of their proteins, subsumed by the term proteome.